Rhythmic Clock Gene Expression in Atlantic Salmon Parr Brain - Bolton, Charlotte M.; Bekaert, Michaël; Eilertsen, Mariann; Helvik, Jon Vidar; Migaud, Herve (Frontiers in Physiology, 2021)
To better understand the complexity of clock genes in salmonids, a taxon with an additional whole genome duplication, an analysis was performed to identify and classify gene family members (clock, arntl, period, cryptochrome, nr1d, ror, and csnk1). The majority of clock genes in zebrafish and Northern pike, appeared to be duplicated. In comparison to the 29 clock genes described in zebrafish, 48 clock genes were discovered in salmonid species. There was also evidence of species-specific reciprocal gene losses conserved to the Oncorhynchus sister clade. From the six period genes identified three were highly significantly rhythmic, and circadian in their expression patterns (per1a.1, per1a.2, per1b) and two was significantly rhythmically expressed (per2a, per2b). The transcriptomic study of juvenile Atlantic salmon (parr) brain tissues confirmed gene identification and revealed that there were 2,864 rhythmically expressed genes (p < 0.001), including 1,215 genes with a circadian expression pattern, of which 11 were clock genes. The majority of circadian expressed genes peaked two hours before and after daylight. These findings provide a foundation for further research into the function of clock genes circadian rhythmicity and the role of an enriched number of clock genes relating to seasonal driven life history in salmonids.